Tumor filoides: Comunicación de un caso clínico y revisión de la literatura - Lahoud Velaochaga, Antonio (2002)
This investigation was performed in Habana city, Cuba, at Calixto García Teching Hospital, on June 2002. The phyloid tomour represents 1 % of total mammarian neoplasias, being a fibroepithelial neoplasia. The histologyc features are: cellularity, mitotic margin, nuclear pleomorphysm, the excessive growing of stoma and infiltrative edges. It is showed a cases of a 52 years old woman, who had a malignant phyloid tomour besides, it is pointed out several considerations on clinical and pathologycal aspects of phyloid tomour.